Education of the Mind and Sustainable Achievement of Business Education Objectives in Nigeria - Stella, PAUL-Mgbeafulike, Vivian; Chidiebere, ALONTA, Gabriel; Agatha, UZOKA, Obioma (Journal of Accounting, Business and Finance Research, 2022)
This study was carried out in Southeast Nigeria to examine education of the mind in the sustainable achievement of business education objectives in Nigeria’s education system. The research used a survey design, and a multistage sampling approach was adopted to select 68 business educators and 206 business education students from Abia and Enugu states. The data collection tool was a closed questionnaire, which was verified by three experts, and a Cronbach’s alpha reliability coefficient of 0.883 was achieved. The data was collected by distributing the questionnaire to 274 respondents. A total of 263 questionnaires were returned fully answered and were considered valid. Data was analyzed using mean and t-test statistics at the 0.05 level. The study identified the importance of 14 significant steps of education of the mind and 15 steps that promote education of the mind for the achievement of business education objectives. The outcome of the survey shows a significant difference (p < 0.05) in the mean values of business educators and students on the importance of education of the mind in achieving business education goals, while no significant difference (p <0.05) was found in the mean values of business educators and students’ responses in the measurement of promoting education of the mind to achieve business education objectives. Based on these findings, it is recommended that teaching strategies should focus on providing students with meaningful mental education.